High xylose yield from stem and external fraction of sugarcane biomass by diluted acid pretreatment - Santos, C.; Bueno, Danilo [UNESP]; Sant’Anna, C.; Brienzo, Michel [UNESP] (Springer Nature, 2020)
Lignocellulosic materials are complex, recalcitrant, and difficult to release fermentable carbohydrates, such as xylose. Xylose is the feedstock for the development of products with high added value, such as ethanol, butanol, xylitol, and furfural. A high xylose yield was obtained from epidermis-free stem and external fraction (containing epidermis) of sugarcane with minimal formation of degradation products using dilute acid pretreatment. The influences of variables such as sulfuric acid concentration (% m/m or % m/v), reaction time (min), and solid/liquid ratio (% m/v) on acid pretreatment were investigated through a central composite design. In study region 1, stem and external fraction had xylose yields of 58.69 and 55.33%, as well as 1.79 and 2.16% of furfural. The optimal condition to obtain high xylose yield was observed with the use of 50% m/m or 1% m/v of sulfuric acid. The highest xylose extraction was achieved in the epidermis-free stem, leading to a less recalcitrant fraction. Xylose has a key role in obtaining products with high added value. For this reason, this study obtained high xylose yield applying optimal conditions of dilute acid pretreatment, with minimum degradation products.
Keywords: Acid pretreatment; Biomass conversion; Renewable feedstock; Sugarcane; Xylose yield